Meningkatkan Motivasi Belajar Anak Berdasarkan Minat Melalui Program Kerja “Bimbelove” di Desa Nanjung RW 04 dan RW 09 - Fulqihayati, Nurathfal Nissa; Ayu, Dyah; Hernahadini, Nelis (Dharma: Jurnal Pengabdian Masyarakat, 2024)
Tutoring is providing material and practical support to children in the field of education based on the child's learning needs and interests, so we strive to solve the urgency of education through the Real Work Lecture work program. The purpose of having tutoring or what we call "Bimbelove" in Nanjung Village is a form of collaborative implementation from various departments which are united in the KKN 16 work program at the Muhammadiyah University of Bandung to increase children's learning motivation by focusing on the children's interests. The method used is 5 stages including data collection and selection of participant subjects, learning sessions, meaningful teaching, character education, assessment and rewards, supervision and mentoring learning. The results of the tutoring work program during 5 meetings at KKN 16 Command Post as many as 18 children in class A (Aged 4-6 years) and class B (Aged 7-12 years) show that the positive development of children's needs in terms of behavioral, humanistic, and cognitive and social so that there is an increase in children's learning motivation in accordance with the interests of each RW.04 and RW.09 tutoring participant in Nanjung Village based on the accumulated appreciation reports, namely: attendance, activeness, skills, communication and attitude with the average score of all children are dominant A (Very Good) and B (Good).